Stress and Coping Mechanism among Nurses Working at Nobel Medical College Teaching Hospital Nepal during Covid 19 Pandemic - Chapagain, Sita (Birat Journal of Health Sciences, 2023)
Introduction: Novel Corona Virus (SARS-CoV-2) is a highly contagious respiratory disease caused by a severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2). Nurses at the frontline of caring for COVID-19 patients are sure to face frequent experiences of mental health challenges. Hence they need special supportive coping strategies to control and reduce their stress.Objective: The aim of this study was to identify level of stress and coping mechanisms used to deal with stress among nurses at Nobel Medical College and Teaching Hospital, Biratnagar, Nepal.Methodology: A cross-sectional study was conducted from August 2021 to February 2022. A total of 300 nurses were selected by using a non-probability consecutive sampling technique. Ethical clearance was taken from the Institutional Review Committee of Nobel Medical College and IRC Registration Number 505/2021. Data was collected by using self-administered questionnaire. The collected data were entered in MS Excel and statistical analysis were processed by the SPSS Version 23. Chi-square test was used to show the association between variables.Results: The findings of the study revealed that out of 300 nurses 91.7% nurses reported moderate and 5.3% reported high level of stress and 92% of nurses used moderate level of coping strategies and only 3.3% of nurses used high level of coping strategies to reduce perceived stress. There was statistically significant association of stress in nurses with marital status, duty schedule and monthly income. Likewise, there was a significant association between living condition of the nurses and coping strategies.Conclusion: The research finding showed all working nurses having some level of stress during the COVID-19 Pandemic. Moreover, about 96% nurses having moderate or high level of stress and in contrast they were also following moderate level of coping strategies. However, they need high level of coping strategies to overcome the persisting stress level.